Rising pattern, Seasonal predisposition and Trend analysis of Animal bite Cases Attending the Anti-rabies Clinic of a Tertiary Care Hospital - Saleem, Sheikh Mohd; Khan, S. Muhammad Salim; Roof, Abdul (Indian Journal of Community Health, 2018)
Background: India is responding to achieve the target of zero human death from dog-mediated rabies by 2030. Objectives: To study the rising pattern, seasonal predisposition and trend analysis of animal bite cases attending the anti-rabies clinic of a tertiary care hospital. Methodology: This retrospective cross-sectional study was conducted in the anti-rabies clinic of Department of Community Medicine, Government Medical College, Srinagar, Jammu & Kashmir. Data were collected from the animal bite register maintained at the said clinic. Data were entered into Microsoft Excel spreadsheet and analysed with the application of mean, proportion and trend analysis. Results: Total number of animal bite cases were 49508 in last 14 years (2004-2017). The rising case pattern has been observed since the year 2009.The maximum number of cases being 7324 in the year 2016 followed by 6548 in the year 2017 respectively. The seasonal predisposition of animal bite cases was seen in the month of March and June. On-trend analysis, forecasting for 2018, 2019 and 2020 showed 7570, 8108 and 8645 cases respectively. Conclusion: We conclude that the animal bite cases are on an increase in the future years and applicable management measures with intersectoral coordination ought to be started vigorously in endemic areas.